Penggunaan Sistem Informasi Enterprise Resource Planning (ERP) dan Komunikasi Verbal terhadap Adaptive Performance - Eneng Ferawati; Erry Sunarya; Resa Nurmala (IPM2KPE, 2024)
This research aims to find out how much influence the use of Enterprise Resource Planning (ERP) Information Systems and Verbal Communication has on Adaptive Performance at PT. Pratama Abadi Industri Sukabumi. The respondents in this study were 36 employees. This research method uses a quantitative method with an associative descriptive approach. This research carried out multiple correlation coefficient analysis, determination coefficient, multiple linear regression analysis, determination coefficient test and hypothesis testing partially (T test) and simultaneously using (F test). The results of this research show that there is a positive and significant influence between the use of Enterprise Resource Planning (ERP) Information Systems on Adaptive Performance. by producing Tcount greater than Ttable, namely (2.069>2.034) with a significance of 0.046>0.05. Verbal communication has a positive and significant effect on adaptive performance, this is proven by the results of Tcount being greater than Ttable, namely (2.063 > 2.034) with a significance of 0.047 > 0.05. The contribution in measuring the influence of the use of Enterprise Resource Planning (ERP) information systems and verbal communication on adaptive performance is 81.9%, while the remaining 18.1% is the influence of other factors outside this research. Keywords: Adaptive Performance, Enterprise Resource Planning (ERP), Verbal Communication